Game Online Higgs Domino di Kota Banda Aceh dalam Perspektif Hukum Pidana Islam - Yuhasnibar; Rahma Wati (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2022)
The people of Banda Aceh City were shocked by the emergence of online-based gambling, namely the higgs domino game. Statistically, there are 3 cases of higgs dominoes that occurred in the people of Banda Aceh City in 2021 and 2022, there are as many as 3 cases that have been heard and have even been executed by whips. However, not a few of the players of this game are free from legal snares or not tracked massively. This fact raises academic anxiety, especially how the game indicators fall into the gambling category or not, especially in the perspective of Islamic Law. This research is a qualitative type through literature studies and field studies with a descriptive analysis approach. Data collection was carried out by observation, interviews, documentation and literature studies by compiling literature sources, both primary and secondary. The results of this study state that; Judging from the Islamic Criminal Law, the higgs domino online game has fulfilled the three elements of gambling (maisir), namely the element of the game being played, the element of profit and the element of betting at stake is chips (virtual coins)